STUDI PENGARUH CORPORATE GOVERNANCE, LIKUIDITAS DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE DI INDONESIA - WULANDARI; MUSDHOLIFAH (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to examine and determine the effect of Corporate Governance, liquidity and profitability onfinancial distress in the sub-sector company property and real estate listed on the Indonesia Stock Exchange(BEI) in 2018. In this study corporate governance is measured indexed by IBCG rating modified, liquidity isproxied by the current ratio (CR), and profitability is proxied by return on assets (ROA). The theory used as thebasis of relationships between variables is agency theory, trade-off theory and du pont theory. The approachused in this research is quantitative with purposive sampling technique. The study sample consisted of 46companies from the sub-sector property and real estate listed on the IDX in 2018. The data of this study weresecondary data taken from the official pages of the Indonesia Stock Exchange and their respective companies.The process of data analysis uses SPSS 23. Logistic regression. The results of this study indicate that corporategovernance does not affect financial distress, liquidity has a significant positive effect on financial distress, andprofitability has a significant positive effect on financial distress. The limitation of this study is that it only usesliquidity and profitability ratios as independent variables among the many financial ratios, besides the studysample is only limited to the sub-sectors property and real estate. So the recommendation given is to usefinancial ratios other than profitability and liquidity and expand the research sample.